Gastric metaplasia and duodenal ulcer disease in children infected by Helicobacter pylori. Issue 4 (April 1996) - Gormally, S M; Kierce, B M; Daly, L E; Bourke, B; Carroll, R; Durnin, M T; Drumm, B
Abstract : BACKGROUND–Helicobacter pylori infection of the gastric mucosa is vital in the pathogenesis of duodenal ulcer disease. H pylori will only colonise gastric epithelium and its association with duodenal disease is therefore not easily explained. AIMS–To determine if gastric metaplasia in the duodenum increases the risk of duodenal ulcer disease in children infected with H pylori. PATIENTS–All children undergoing upper endoscopy over a 20 month period in a children's hospital in Ireland. METHODS–Two biopsy specimens were obtained from the antral mucosa and two from the first part of the duodenum. One antral biopsy specimen was used in a rapid urease test (Clo Test). Biopsy sections were stained with haematoxylin and eosin and also with cresyl violet for identification of H pylori. Periodic acid Schiff (PAS) stain was performed to identify areas of gastric metaplasia. RESULTS–Gastric and duodenal biopsy specimens were obtained from 148 patients (M:F 1:2:1). Twenty five children (17%) had H pylori positive gastritis. Thirty four children (23%) had gastric metaplasia in the duodenum. Nine per cent of children under the age of 8 years had gastric metaplasia compared with 38% in those 12 years of age or over (p < 0.005). Seven children had duodenal ulcer disease. Gastric metaplasia was present in six of seven (86%) children with duodenal ulcer disease compared with 28 of 141 (20%) without ulceration (p < 0.001). While both H pylori and gastric metaplasia were each significant risk factors for duodenal ulcer disease, the combined presence of both factors was associated with a pronounced increase in duodenal ulcer disease. Duodenal ulcer disease occurred in over 50% of children with both H pylori infection and gastric metaplasia. In contrast duodenal disease did not occur in children (0 of 100) when both were absent. CONCLUSION–The presence of gastric metaplasia in the duodenum is the major risk factor for duodenal ulcer disease in patients colonised by H pylori.